2009
DOI: 10.1007/s10571-009-9441-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Saffron Extract and Crocin on Reactive Oxygen Species-Mediated High Glucose-Induced Toxicity in PC12 Cells

Abstract: Diabetic neuropathy is one of the most frequent complications of diabetes. Despite some studies, the exact mechanism of glucose neurotoxicity has not been fully elucidated. Increased reactive oxygen species (ROS) has proposed as a possible mechanism. Crocus sativus L. (saffron) has been known as a source of antioxidants. Therefore, neuroprotective effect of saffron extract, its active component crocin and gamma-glutamylcysteinylglycine (GSH) was studied in glucose-induced neurotoxicity, using PC12 cells as a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(70 citation statements)
references
References 30 publications
3
63
0
4
Order By: Relevance
“…Crocin, a major carotenoid of saffron, exhibits high antioxidant and scavenging properties in vitro and in vivo (Ochiai et al 2004a(Ochiai et al , b, 2007Hosseinzadeh et al 2009Hosseinzadeh et al , 2010Mousavi et al 2010). For instance, Crocin has been shown to attenuate lipid peroxidation in kidney (Hosseinzadeh et al 2005) and skeletal muscle (Hosseinzadeh et al 2009) during ischemia-reperfusion-induced oxidative damage in rats and to promote cell viability in PC12 cells (Mousavi et al 2010). Our results indicate that, as effective free-radical scavengers and antioxidants, Quercetin and Crocin reduce ZEN toxicity in HCT116 and HEK293 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crocin, a major carotenoid of saffron, exhibits high antioxidant and scavenging properties in vitro and in vivo (Ochiai et al 2004a(Ochiai et al , b, 2007Hosseinzadeh et al 2009Hosseinzadeh et al , 2010Mousavi et al 2010). For instance, Crocin has been shown to attenuate lipid peroxidation in kidney (Hosseinzadeh et al 2005) and skeletal muscle (Hosseinzadeh et al 2009) during ischemia-reperfusion-induced oxidative damage in rats and to promote cell viability in PC12 cells (Mousavi et al 2010). Our results indicate that, as effective free-radical scavengers and antioxidants, Quercetin and Crocin reduce ZEN toxicity in HCT116 and HEK293 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The high antioxidant capacity of Crocin has been reported in vitro and in vivo (Ochiai et al 2004a(Ochiai et al , b, 2007Hosseinzadeh et al 2009Hosseinzadeh et al , 2010Mousavi et al 2010). For example, Crocin can decrease lipid peroxidation in kidney (Hosseinzadeh et al 2005) and skeletal muscle (Hosseinzadeh et al 2009) during ischemiareperfusion-induced oxidative damage in rats.…”
Section: Introductionmentioning
confidence: 97%
“…A series of studies demonstrated that crocin can diminish the extent of MDA generation [35], reduce intracellular ROS production [36] and increase SOD and GSH peroxidase enzyme activity [37,38]. Moreover, in an vivo study, El-Beshbishy et al [39] found that pretreatment with crocin (200 mg/kg i.p.)…”
Section: Discussionmentioning
confidence: 99%
“…[85] Assimopoulou et al [80] found methanolic crocin solution from C. sativus L. to have high radical scavenging activity, whereas Soeda et al, [9] suggested a Glutamate Dehydrogenase, GDH-dependent mechanism for crocin protective effect against stressinduced cell death. Mousavi et al [86] reported reduced ROS production in glucose-induced neurotoxicity in PC12 cells pretreated with 10-50 μμ of crocin. The latter yield confirms the previous results of Ordoudi et al [87] who reported that saffron extract is equally efficient to phenolic antioxidants in reduction of intracellular ROS production in human monocyte system.…”
Section: The Antioxidant Activity and Properties Of Saffronmentioning
confidence: 99%